Key elements in the quality assessment of a type 3 medication review - Robberechts, Anneleen; Michielsen, Melissa; Steurbaut, Stephane; De Meyer, Guido R. Y.; De Loof, Hans (Frontiers in Pharmacology, 2023)
The survey was completed by 95 participants, including 42 PRISMA pharmacists, 19 APA pharmacists, 18 KAVA pharmacists and 16 pharmacy students. Opinions from participants from the different groups overlapped significantly. The use of simple and understandable language in the conversation with the patient was considered essential by the majority. Discussing the usefulness and purpose of a MR3 with the patient was also rated highly by all groups. Differences of opinion were present in aspects about laboratory values, the use of specific tools, and reporting to and consultation with the treating physician. The participants themselves formulated a limited number of additional assessment criteria.There was widespread agreement on the hierarchy of the quality assessment criteria for MR3s. Minor differences were related to the experience of the participants. With these results and a small number of suggested extra criteria, a quality assessment instrument for MR3 can be created.